Modeling and Parametric Analysis of a Large-Scale Solar-Based Absorption Cooling System - Ali Abdullah; Abdullah A. AlZahrani (Modelling and Simulation in Engineering)
This study investigates the thermodynamic performance of a solar-powered absorption cooling system. The system uses a lithium bromide-water (LiBr-H2O) absorption refrigeration system (ARS) integrated with evacuated solar collectors (ETSC) and thermal energy storage (TES) to provide a 3 kTR cooling capacity for a university campus. The paper examines the performance of the integrated system under different design and operating conditions as well as the performance of each subsystem, i.e., ETSC, TES, and ARS. Furthermore, a parametric energy and exergy analysis is applied, where different parameters are studied, such as the temperatures of the generator, the condenser, the evaporator, and the absorber. In addition, the system performance is examined with the variation in environmental conditions. The coefficient of performance (COP), exergetic efficiency, exergy destruction, and fuel depletion ratio (FDR) are used to evaluate the system’s performance. The ETSC and the TES are studied under the variation in solar radiation through the day in two seasons: summer and winter. The results revealed that the increase in generator temperature positively impacts the COP of the ARS while lowering the condenser and absorber temperature gives the same positive effect. Furthermore, the main reason for the exergy destruction is found to be the solar collector, which is responsible for destroying 89% of the input solar exergy. Additionally, 4.7% of the inlet exergy is destroyed in the generator, which makes 4.5% of the total exergy loss. The TES destroyed 4.8% of the total solar exergy input. The energy analysis shows that the ARS achieves an energetic COP of about 0.77, while the exergy analysis revealed that the exergetic COP is 0.21.